Malaria knowledge, prevention practices, and insecticide-treated net ownership and use among foreign migrants: A survey in four malaria transmission districts of Yala Province, Southern Thailand - Naing, Tinzar; Rattananupong, Thanapoom; Hiransuthikul, Narin (Chulalongkorn Medical Journal, 2021)
Background: Increased malaria caseload is a public health threat to malaria elimination in Southern Thailand. Yala Province has the second highest malaria caseload in the country. Cross-border migration may be an underlying reason for the malaria outbreaks in Yala. Objectives: In this study, we aimed to assess the malaria knowledge, prevention practices, and insecticidetreated net (ITN) ownership and use among migrants in four malaria transmission districts of Yala Province. Methods: We conducted a cross-sectional survey with two-stage cluster sampling recruiting 414 migrants. We identified migrants’ locations with the help of key informants. Migrants aged 18 years and older were interviewed face-to-face to collect information using a structured questionnaire by trained volunteers. Results: Mean age was 29.9 ± 7.2 years and 71.5% were men. Of the surveyed population, 72.1% had heard of malaria and 47.9% knew about malaria prevention methods. Among the four districts, perceived susceptibility to malaria was highest in Yaha District; perceived severity of malaria and benefits of using ITNs were highest in Than To and perceived barriers to ITN use were highest in Bannang Sata District. Sixty-two point nine percent of migrants possessed a net and 40.7% owned an ITN, but only 14.1% used an ITN every night. ITN use more than 5 days a week and every night was significantly different among districts with the most migrants in Kabang District (44.8%, P = 0.015) and Yaha District (17.8%, P = 0.046) respectively. Conclusions: This survey provides data to assist with malaria elimination in Thailand. ITN coverage should be improved among migrant populations in Yala. Behavioural change communication messages targeting migrant populations should focus on the benefits of sleeping under an ITN.